EFFECT OF WORK DISCIPLINE, LEADERSHIP STYLE AND TRAINING ON EMPLOYEE PERFORMANCE IN RSUD HAJI MAKASSAR - Yusrab Ardianto Sabban; Masyadi Masyadi (Universitas muhammadiyah malang, 2020)
The purpose of this study was to analyze the effect of work discipline, leadership style, and training on device performance partially and simultaneously, and to analyze which variables had the most dominant influence on the performance of the employees of RSUD Haji Makassar. The sample of this study was 120 people, using saturated samples, with the method of multiple linear regression analysis with the help of the SPSS program. The result showed that employee performance is influenced by work discipline, leadership style and training. The variable that has the most dominant influence on the performance of employees at RSUD Haji Makassar is training. Therefore, it is recommended to allocate funds for training activities and develop an incentive policy for fostering responsibility and employee integrity.